Análisis para establecer la automatización en las redes de distribución de CNEL Los Ríos. - Franco Delgado, Julio Cesar (2022)
The electrical service constitutes one of the fundamental elements on which the economies are developed. Customers want a reliable, safe and affordable service. The Electric Companies seek to improve the quality of service, reduce costs and simplify the operation. The automation of electrical systems responds to these needs. The objective of this technological proposal is to automate the electrical distribution networks of the National Electricity Corporation CNEL EP, in which it has a high number of clients that use the public electricity supply service, unfortunately the current processes to carry out maneuvers in the distributor they are manually, in addition there is no exhaustive control of the information. Automation in electrical networks has become a requirement essential for its proper functioning. The primary electrical equipment together with its Measurement, communications, control and protection subsystems ensure the reliability and availability of the Substations. The proposal will be used for some strategic areas that make up the company and thus the processes are fast and safe. Finally, it will be possible to automate and optimize the time of disconnections.